A codon-pair deoptimized live-attenuated vaccine against respiratory syncytial virus is immunogenic and efficacious in non-human primates. Issue 14 (23rd March 2020) - Mueller, Steffen; Stauft, Charles B.; Kalkeri, Raj; Koidei, Fusataka; Kushnir, Anna; Tasker, Sybil; Coleman, J. Robert
Abstract: Despite a critical need for a respiratory syncytial virus (RSV) vaccine and decades of development efforts, a vaccine to protect infants, elderly, and other at-risk populations from RSV infection remains elusive. We have previously generated a new, live-attenuated vaccine candidate against RSV using rational, computer-aided gene design and chemical synthesis through a process termed viral gene "deoptimization ." In this study, we assessed the attenuation, immunogenicity, and efficacy of this synthetic, live-attenuated RSV vaccine candidate, RSV-MinL4.0, in African Green Monkeys. RSV-MinL4.0 was produced under good-manufacturing-practice (GMP) in Vero cells. Vaccination with RSV-MinL4.0 resulted in minimal virus shedding after vaccination, generation of robust humoral and cellular immune responses (despite the presence of baseline RSV neutralizing antibodies in one animal) that were comparable to a wildtype infection, and protection from virus shedding post-challenge with wildtype RSV. These findings demonstrate the promise of RSV-MinL4.0 as a live-attenuated vaccine which will undergo clinical trials to test its ability to safely and effectively protect pediatric and elderly populations from infection with RSV.